If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -7x = 213 + -42x Solving 13 + -7x = 213 + -42x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '42x' to each side of the equation. 13 + -7x + 42x = 213 + -42x + 42x Combine like terms: -7x + 42x = 35x 13 + 35x = 213 + -42x + 42x Combine like terms: -42x + 42x = 0 13 + 35x = 213 + 0 13 + 35x = 213 Add '-13' to each side of the equation. 13 + -13 + 35x = 213 + -13 Combine like terms: 13 + -13 = 0 0 + 35x = 213 + -13 35x = 213 + -13 Combine like terms: 213 + -13 = 200 35x = 200 Divide each side by '35'. x = 5.714285714 Simplifying x = 5.714285714
| 2(3n+3)=-10 | | -9=3x+9 | | 13*21= | | 6y^2-19y+15=0 | | 85-6x=10-7x | | x^3-x^2-10=0 | | 96-3x=5x+8 | | X+4=3x-6 | | (12-4x)+(5-7x)=23 | | x^3+3*x+2=0 | | y=28-3(6) | | y=28-3(5) | | y=28-3(3) | | y=28-3(2) | | 20=40-4f | | 3(k+4)=12k-6 | | 6X+20=14x-68 | | x-6y=3v | | 76-7x=29x+16 | | 2x=8+2 | | 8(x+1)=2(x-2) | | 94-2x=25x+19 | | 8x-4=58 | | 7z-2=3z+6 | | 10-8x=82-29x | | 7x+5=54 | | 15-4e=3 | | 3e-3=18 | | 4x=88 | | 6x=88 | | -15-2x=13-9x | | 3y+3=18-2y |